FERGANA IN THE VALLEY BEING CARED FOR BEES RACES COMPOSITION AND BEE BREED SELECTION - Jamalov Rapikjon Kushmatovich (Web of Journals Publishing, 2025)
The choice of bee breeds in beekeeping depends on the purpose for which the bee colony will be used. If a bee colony is to be acquired for the purpose of producing commercial honey, it is advisable to select bee breeds that produce a lot of honey.
Keywords: Bee breeds, breeding, Central Russian, Carpathian, Italian, Carnic, Buckfast, queen bees, productive, 1st and 2nd class, race, population, hornet, package, tergite, cubital.